Media and Ethnicity in the 2012 General Elections - A.D. , Orawo; P., Kutoto; S., Owuor (African Journal of Education,Science and Technology (AJEST), 2015)
The 2013 general elections came at a period when Kenyan was still recovering from the effects of the 2008 Post Election Violence. This was the worst political crisis ever witnessed in the country‟s history since independence. Despite the fact that the healing process was still taking place and the new constitution yet to be fully implemented, issues of ethnicity seemed to be playing a major role in political rallies and presidential campaigns. This was further heightened by the media which kept on reporting negative ethnicity. The purpose of the study was therefore to establish whether the media contributes to ethnic polarization through the manner in which they cover political election campaigns. The study was informed by Agenda setting theory and the Critical Political Economy theory which govern media reporting of political issues. This study adopted a qualitative research design that targeted print media. Articles from the Daily Nation Newspapers starting from November 2012 to February 2013 were purposively sampled so as to give a representation of media reports. A total of 36 newspapers were used to collect data. The newspaper articles were coded according to themes using word matching and presence of acceptable synonyms or similar phrases. The study used content analysis as a means of analyzing the relevant data. The study established that the media adopted technique of using language and words that is largely based on ethnic politics, that politicians used the media to manipulate the norms in their favour and that presidential candidates perceived to have tribal backing from their communities, made it to the headline news more often than other candidates. The findings from this study will be able to provide direction to media scholars and social scientists that are assisting the media institutions to find alternative roles the media can play in the production of political news without stimulating or enforcing the trends of negative ethnicity.